The comics about Asterix as a way of representing modernity - Albina Marselevna Imamutdinova, Liudmila Mihajlovna Shmeleva, Gutman Evgeniya Vladimirovna,; Victorovitch Shmelev, Dmitry (Opción, 2019)
The article considers the semantic allusions of French comics about Asterix via the interpretative and inductive-deductive method and linguistic-semiotic analysis of the comic’s text. As a result, Comics about Asterix came out against the background of powerful sociocultural changes in French society, which affected their content. The authors of the article concluded that the following modern markers can be identified in Asterix comics: France political reality (election campaigns, major political figures, attitude to collaborationism, attitude to modern republican culture and state structure); feminism and attitude to it from the French society; stereotypes of national behavior and self-identification of the French.